E-modulus evolution and its relation to solids formation of pastes from commercial cements - Maia, Lino (2012)
Models for early age E-modulus evolution of cement pastes are available in the literature, but their validation is limited. This paper provides correlated measurements of early age evolution of E-modulus and hydration of pastes from five commercial cements differing in limestone content. A recently developedmethodology allowed continuous monitoring of E-modulus from the time of casting. The methodology is a variant of classic resonant frequencymethods,which are based on determination of the first resonant frequency of a composite beam containing the material. The hydration kinetics — and thus the rate of formation of solids — was determined using chemical shrinkagemeasurements. For the cements studied similar relationships between E-modulus and chemical shrinkage were observed for comparable water-to-binder ratio. For commercial cements it is suggested to model the E-modulus evolution based on the amount of binder reacted, instead of the degree of hydration.